Analisis Pertimbangan KPPU Terhadap Pelanggaran Persaingan Usaha Tidak Sehat Dilakukan Oleh Perusahaan Penerbangan BUMN (Studi Kasus Putusan No. 15/KPPU-I/2019) - Faisal Fachri; Iwan Erar Joesoef (Jurnal Cahaya Keadilan, 2021)
State-Owned Enterprises (SOEs) has a role to improve the nation's economy is very central, in the implementation of SOEs are excluded to monopolize market share based on the Act based on article 33 Paragraph (2) of the 1945 Act basically can be excluded in certain sectors with the welfare of the people, however, in practice, monopolistic practices are often found that are not in accordance with the stipulated regulations. Aviation companies under the auspices of SOEs are necessary considering that the aviation sector is very much needed by the community. This journal examines business competition in BUMN monopolies. This study aims to understand the concept of monopoly carried out by SOEs in the aviation sector and efforts to overcome it. The method used in this research is a normative juridical approach which in the main data processing uses secondary data, namely data obtained from literature reviews. The approach used in solving problems is per se illegal. A good corporate government can be a reference for KPPU in determining the limits of activities in monopoly carried out by SOEs. The type of research carried out in this research is legal research (legal reseacht), namely research that examines the formulation of the problems contained in the research by examining the relevant regulations that apply. Keywoard: